Pengaruh Social Media Influencer, Brand Image, Dan Brand Awareness Tehadap Keputusan Pembelian Pada Produk Facetology Di Kabupaten Trenggalek - Devitasari, Amelia Putri; Khalikussabir, Khalikussabir; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of Social Media Influencer, Brand Image, and Brand Awareness on Purchase Decisions of Facetology products among the local community, particularly in Trenggalek Regency. Facetology is a local skincare brand that has started to gain recognition through digital marketing strategies that rely on the power of social media. This research uses a quantitative approach with a survey method, distributing questionnaires as the primary instrument for data collection. The sample consisted of 90 respondents selected using purposive sampling. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results of the study partially indicate that Social Media Influencer (X1), Brand Image (X2), and Brand Awareness (X3) have a positive and significant effect on Purchase Decision (Y). These findings suggest that digital marketing strategies through influencers, as well as strengthening brand image and awareness, play an important role in influencing consumer purchasing decisions, especially for local skincare products such as Facetology. Keywords: Social Media Influencer, Brand Image, Brand Awareness, Purchase Decision, Facetology.